Influencia de la gestion administrativa en la gestión de la práctica pedagógica en la Institución Educativa Secundaria N°60057 Petronila Perea De Ferrando-2024 - Vilchez Ramirez, Jaime (2024)
In the educational field, administrative management and pedagogical practice are essential for the effective functioning of institutions and the achievement of learning objectives. Although interconnected, these areas have distinct functions that drive the development of the educational community. This study explored the influence of administrative management on pedagogical practice at Secondary Educational Institution No. 60057 Petronila Perea de Ferrando - 2024, using a non-experimental, descriptive-correlational approach without variable manipulation. Seventy primary and secondary teachers were surveyed, yielding data with a 95% confidence level that demonstrated a significant influence of administrative management on pedagogical practice. The findings highlight that effective administrative management creates a favorable teaching environment by providing resources, promoting collaboration, and fostering critical reflection. At this institution, administrative strategies have supported continuous training, collaborative work, pedagogical reflection, and teaching innovation. This is reflected in teachers' positive perceptions of administrative management and its impact on the dimensions of teaching management evaluated. The relationship between these two areas is complex and multifaceted, requiring further research to better understand the specific mechanisms of this interaction and identify optimal practices to enhance their synergy. These results underscore the importance of administrative management in promoting educational quality, positioning it as a key factor in strengthening pedagogical practice and, consequently, educational success. In conclusion, this study reaffirms that effective administrative leadership is crucial for developing high-quality pedagogical practices, significantly contributing to the comprehensive and sustainable development of the educational community.